Inositol 1,4,5-trisphosphate-gated channels in cerebellum: presence of multiple conductance states - Watras, J (J Neurosci, 1991)
The mechanism by which inositol 1,4,5-triphosphate (InsP3) induces calcium (Ca) release from the reticulum of canine cerebellum was examined. Reticular membrane vesicles used in these experiments accumulated Ca in the presence of ATP and then released approximately 30% of the accumulated Ca upon addition of micromolar concentrations of InsP3. When these membrane vesicles were incorporated into planar lipid bilayers, InsP3-gated Ca channels were observed. Up to four current amplitudes were observed at a given voltage, yielding conductances of 20, 40, 60, and 80 pS with 50 mM Ca as the current carrier. Thus, the cerebellar InsP3-gated Ca channel exhibits four conductance levels that are multiples of a unit conductance step. Moreover, examination of the single-channel records showed both openings directly to each of the current levels and rapid transitions between current levels. These four conductance steps may reflect the interaction among the four InsP3 receptors thought to comprise the InsP3-gated Ca channel in these tissues. Examination of the InsP3 dependence of channel openings and Ca release from vesicles, however, yielded Hill coefficients of 1-1.3. Thus, we hypothesize that it takes only one molecule of InsP3 to open the channel. The observation that the conductance of the InsP3-gated Ca channel assumes four levels that are multiples of a unit conductance suggests that the number of interacting InsP3 receptors in one complex can vary from one to four and supports the hypothesis that the channel is a tetramer.